Synthesis and characterization of thermally stable and flame retardant poly (benzoxazine-co-urethane) matrices. Issue 9 (2nd September 2018) - Selvi, Mohan; Devaraju, Subramani; Alagar, Muthukaruppan
Abstract: The flame-retardant behavior of organic polymers is considered as very important criteria to utilize them in the form of coatings, encapsulants, sealants, and matrices for high performance industrial applications. A new type of poly (benzoxazine-co-urethane) (PBZ-co-PU) matrices have been developed using dimethylol benzoxazine monomers (BZM and BZE) and tris(p-isocyanatophenyl)thiophosphate (Desmodur) through A2  + B3 approach followed by thermal curing. The molecular structure of developed PBZ-co-PU was confirmed by FT-IR spectra and their thermal stability and flame retardant behavior were studied by standard methods. Data obtained from TGA and DSC, indicate that the PBZ-co-PU possesses higher Tg, better thermal stability and LOI than those of neat PBZ. Further, it was also observed that among the two matrix systems (PBZ-co-PU-1 and PBZ-co-PU-2) studied, the PBZ-co-PU-1 based system exhibited higher Tg, thermal stability and flame retardant behavior than those of PBZ-co-PU-2.